Shift work disorder and related health problems among nurses working in a tertiary care hospital, Bangalore, South India - Anbazhagan, Surekha (Indian J Occup Environ Med, 2016)
INTRODUCTION: Shift Work Disorder (SWD) is a sleep disorder characterized by sleepiness and insomnia, which can be attributed to the person's work schedule. Awareness of the mechanisms behind shift work related health problems could be essential to schedule the shift work, employment routines, clinical treatment, and selection of employees. OBJECTIVE: To assess the prevalence of SWD and to identify related health problems among nurses in a tertiary care hospital in Bangalore. MATERIALS AND METHODS: We conducted a descriptive cross-sectional study in a tertiary care hospital in Bangalore between May and September 2014. Based on simple random sampling, 130 nurses were selected for the study. After obtaining written informed consent from the participants, structured interview schedule using Standard Shift Work Index and Bergen Shift Work Sleep Questionnaire (BSWSQ) was administered. RESULTS: The mean age of the 130 nurses was 27.4 ± 2.64 years. The prevalence of SWD was found to be 43.07%. Headache, back pain, gastritis, and menstrual disorders were the most common complaints, which are found in 78 (60.0%), 75 (57.6%), 42 (32.3%), and 39 (30.0%) cases, respectively. Anxiety and depression was found in 23 (17.6%) and 31 (23.8%) individuals, respectively. We also found a significant association of SWD with increasing age, more number of nights worked in a year, and longer duration of working hours. According to the BSWSQ, 70 (53.8%) nurses were found to have sleep problems. CONCLUSION: A high prevalence of SWD symptoms calls for a focus on the antecedents of work related sleep problems and appropriate intervention, such as behavioral changes, clockwise rotating shifts, and treatment.